Swine Carcass Disposal Options for Routine and Catastrophic Mortality - Harper, Allen F.; DeRouchey, Joel M.; Glanville, Thomas D.; Meeker, David L.; Straw, Barbara E. (Council for Agricultural Science and Technology (CAST), 2008)
This Issue Paper provides a critical assessment of information available on methods of swine carcass disposal under routine and catastrophic conditions. The authors have focused on efficiency and effectiveness of available methods as well as potential animal health and environmental protection considerations. The paper addresses the four predominant methods of mortality disposal in commercial swine production–burial, incineration, rendering, and composting–and various alternative and nontraditional methods and technologies.
Keywords: Swine Carcass Disposal; Catastrophic Mortality; Swine Mortality